The descriptions of phrasal verbs in language reference materials - Kamarudin, Rafidah; Md Zamin, Ainul Azmin (Australian International Academic Centre, 2018)
Multi-word units like phrasal verbs (PVs) are very common in English, indicating their usefulness in everyday settings. Despite the importance of PVs in both written and spoken discourse, it was reported that language learners generally have great difficulties in understanding and using this linguistic form due to various factors. However, studies examining the treatment of PVs in language reference materials, which may also contribute to learners’ difficulties in understanding PVs are still lacking. Thus, the present study investigates how language reference materials, in particular those commonly prescribed to Malaysian school learners, address and describe this very common and important linguistic feature. Secondary school prescribed textbooks and two learner dictionaries were examined. All sections in the textbooks and dictionaries entries that discuss the selected common PVs were analyzed. Descriptive analysis was conducted to examine how this particular language form is described by looking at the selection of PVs, as well as information provided with respect to PVs. Results of the present study have revealed a number of useful findings with regard to the selection and description of PVs in both reference materials which to date, have not been found in any other studies in Malaysia, to inform relevant parties for further actions